Resveratrol acts via melanoma-associated antigen A12 (MAGEA12)/protein kinase B (Akt) signaling to inhibit the proliferation of oral squamous cell carcinoma cells. Issue 1 (1st January 2021) - Shang, Yu; Jiang, Yu-Ling; Ye, Li-Jun; Chen, Li-Na; Ke, Yue
ABSTRACT: The present study examined how resveratrol affects cell growth and MAGEA12/Akt signaling pathway in OSCC cells. Cal-27 cells were transiently transfected with a plasmid encoding MAGEA12, and the effects of overexpression were assessed in terms of cell viability, colony formation and the epithelial–mesenchymal transition. Cal-27 cells and MAGEA12 -overexpressing cells were treated with resveratrol, then the cell viability and colony formation were also assessed by CCK8 assay and microscope, respectively. Levels of MAGEA12, p-Akt, Akt, Cyclin D1, and CDK14 genes and these proteins were analyzed using quantitative reverse-transcription polymerase-chain reaction and western blot. In the present research, we first generated and transiently transfected MAGEA12 plasmid into Cal-27 cells. Our results suggested that overexpressing MAGEA12 led to an increase in levels of phospho-Akt, which was associated with increased cell viability, colony formation. Moreover, overexpressing MAGEA12 also resulted in the up-regulation of Cyclin D1 and CDK14, indicating MAGEA12 induces the cell proliferation of Cal-27 cells. In addition, these effects were partially reversed by inhibiting Akt. Furthermore, resveratrol could inhibit the proliferation and colony in Cal-27 cells and decrease the expressions of MAGEA12 and p-Akt depending on the time and concentration. These effects were also partially reversed by MAGEA12 overexpression and Akt activation. In summary, resveratrol may suppress the growth of OSCC cells by inactivating MAGEA12/Akt signaling. These findings suggest that resveratrol may be a therapeutic drug for OSCC in clinical. GRAPHICAL ABSTRACT: uf0001